Crossing Thresholds in The House of the Seven Gables: Hawthorne’s Narrative Architecture and the Encounter with History - Woodard, Luke (Nathaniel Hawthorne Review, 2025)
ABSTRACT. This article examines the formal significance of the threshold trope in The House of the Seven Gables. While readers and critics alike have long noted the threshold’s thematic importance to the story, Luke Woodard reads the architectural image as a metaphor for the novel’s narrative structure. Just as the novel’s characters are constantly stepping back and forth across the literal thresholds of the Pyncheon-house, Hawthorne employs a variety of unconventional narrative techniques to dramatize the reader’s crossing into the fictional world of his story. In doing so, Hawthorne recreates for his audience a similar process to what Clifford and Holgrave undergo over the course of the story, urging the reader to move beyond a binary conception of past and present. In the final section of the article, the author argues that the House of the Seven Gables Settlement Association and Museum in Salem currently stands as both a result and continuation of Hawthorne’s narrative technique. Woodard’s approach sheds light on the extent to which the self-reflexive formal structures of Hawthorne’s fiction are connected to his work as a writer of historical romance.
Keywords: dept.eng

Introduction: The House of the Seven Gables in Ink, Wood, and Stone - Baraw, Charles (Nathaniel Hawthorne Review, 2025)
Best-selling author Alice Hoffman’s 2023 magic-realist-bio-fiction, The Invisible Hour, features a very visible Nathaniel Hawthorne as the romantic lead. Set in the twenty-first century and in Hawthorne’s time, the story unfolds in Concord, Salem, and the Berkshires, all places Hawthorne lived. At a crucial moment in the contemporary story, the protagonist, Mia Allen, flees her abusive stepfather, who has chased her from his fundamentalist cult in the Berkshires to New York City then to Concord and to Salem—her last hope of escape. Once there, she runs directly to the House of the Seven Gables. Mia believes she might return to her beloved author, if she can reach the house where he was born. It might be another portal to the past, like “Sleepy Hollow Cemetery” in Concord, where she first traveled back in time to meet Hawthorne. Unfortunately, when she gets to the museum on Turner Street, a summer intern, “who had written a paper on The House of the Seven Gables,” has already locked the gate (Hoffman 209).1 Visiting hours are over.I start my introduction to this special issue of the Nathaniel Hawthorne Review, “The House of the Seven Gables in Ink, Wood, and Stone,” with an example from a modern prequel to The Scarlet Letter to illustrate how a central paradox about the House persists to our day: the House of the Seven Gables is real and not real. In The Invisible Hour, Mia Allen runs toward one of the most popular cultural and literary tourist sites in the United States (voted “Best Historical Home Tour” in 2025 by Newsweek magazine). When Hoffman brings Mia to Salem, she can be confident that her novel’s readers may be among the more than one hundred thousand people who visit the museum each year. This is the House of the Seven Gables as a recognizable cultural icon, a vibrant contemporary institution and an engine of economic activity in Salem’s postindustrial economy. Or rather, this is the House of the Seven Gables in “Wood” and “Stone”: a complex of antiquarian buildings, gardens, and grounds—tangible, visitable, real.Yet once Hoffman gets Mia inside the gates of the museum, a haze, fog, or something intangible descends, and she promptly disappears from the twenty-first century—becoming invisible to the hapless intern—“and nothing was as it had appeared to be” (Hoffman 209). This is the House of the Seven Gables in “Ink”—a fiction whose magic derives from the afterlife of Hawthorne’s original text. Things happen there that we might not expect in a crowded house-museum tour. Hoffman’s House of the Seven Gables becomes a literary habitation: a house as metaphor, extending across time and space. Mia, too, becomes a symbolic figure and a contemporary embodiment of the ideal reader. She makes visible our metaphors for reading as immersion and imagined presence in a world elsewhere. Her love affair with Nathaniel Hawthorne dramatizes both the contemporary popularity of romance and the history of “author love” that scholars have recognized as a powerful aspect of canon formation and literary reception.2 Hoffman’s Hawthorne—a love-object and a romantic lead, a canonical author yet still unknown, a historical person and a fictional afterlife—is himself real and unreal.An ontological ambiguity between fact and fiction has characterized the reception of the house on Turner Street in Salem since it was first called the House of the Seven Gables (now the Turner-Ingersoll House, the centerpiece of The House of the Seven Gables Museum). Within the decade following Hawthorne’s death, his readers had made the house on Turner Street, along with “The Hawthorne House” (the birthplace on Union Street) and the Custom-House, a destination for literary pilgrimages. From the start, though, this popular mode of literary reception sparked a debate about the house’s status. George Parsons Lathrop takes a side in his 1876 Study of Hawthorne, acknowledging “some slight controversy as to the original of the visionary mansion” before denying misguided attempts to locate any original (235). In his “Introductory Note” to the 1883 Riverside edition of The House of the Seven Gables, Lathrop doubles-down against the “hundreds of pilgrims annually” who visit the Turner Street house and the “delusion that there must have been a single original House of the Seven Gables, framed by flesh-and-blood carpenters” (xiii, xii). In 1880 Thomas Franklin Hunt and Henry Morrill Batchelder published the first edition of the Visitors’ Guide to Salem,3 designed to capitalize on growing tourist interest in Salem. Hunt and Batchelder agreed with Lathrop, denying the existence of the House of the Seven Gables: “Inquiries are frequently made for ‘the House of the Seven Gables,’” and “it would be very pleasant to direct admirers of the great writer to such a house, but as a matter of fact none exists or ever has existed.” Despite the evident demand, the Guide would not indulge the fantasies of literary pilgrims, who insist on a standing, tangible original of Hawthorne’s fictive house. Nevertheless, the 1880 Guide observes that “Turner street is one of the oldest in the city,” and “the stranger will not find that his time has been wasted if he takes a stroll to the old house.” The “old house,” the Guide obligingly points out, “is the last house on the right-hand side going from Derby street,” helpful directions to a House of the Seven Gables that is curiously there and not there (47).By the time Henry James visited Salem in the fall of 1904, pilgrimages by literary tourists were thriving. The Upton family had hung out a sign on Turner Street, charged admission for tours of “The House of the Seven Gables,” and sold souvenirs. Frank Cousins had produced an attractive photo-collage, “Souvenir of Hawthorne’s House of the Seven Gables,” featuring what became iconic images of “Hawthorne,” “The Birthplace,” “The Old Pump,” “The House of the Seven Gables,” and the “Grimshawe House,” and sold many others at his Essex Street shop.4But the “slight controversy” between those who came to visit the house of wood and stone and those insisting it existed only in ink and imagination continued. Text from the 1880 Guide denying the existence of the House of the Seven Gables was reproduced and expanded in several more editions. Repeating an argument from 1895, the 1902 edition of the Visitors’ Guide to Salem (advertised as the “forty-fifth thousand”) states: “‘The House of the Seven Gables’ it is useless to search for, except within the covers of the fascinating book so named” (9). This edition, the most current when James visited, also reprints a more elaborate denial from the 1895 edition, citing a description of the house in Hawthorne’s 1837 story “Peter Goldthwaite’s Treasure” as textual evidence that Hawthorne used multiple sources for the Seven Gables. The 1902 Guide claims “the frame, so to speak, of the ‘House of the Seven Gables’ seems first to have been constructed” in this early story. Though the House of the Seven Gables may not be real, literary pilgrims will find other destinations in Salem to safely identify with Hawthorne’s texts. As the Guide graciously concludes, “there are . . . so many references in [The House of the Seven Gables] to real places . . . it is not surprising the mythical is mistaken for the real by unsuspecting readers” (10).Whether delusional, “useless,” or the folly of the “unsuspecting,” it is precisely the mistaking of the “mythical” for the “real” that makes the persistence of the nineteenth- and early twentieth-century search for an original House of the Seven Gables relevant today. These literary tourist practices are reading practices, as the continuous efforts to discipline and direct them indicate. The condemnations of the “useless search” for a tangible real are consistent with early endeavors to shape Hawthorne’s reception and train readers to read him as the great “Romancer.” What critics, canon-makers, and even guidebook writers do not seem to realize is that literary pilgrimages are a form of romance, a practice that performs on the streets of Salem the blending of the “actual” and the “ideal” advocated by Hawthorne on so many different occasions. Literary tours are extratextual extensions of practices applied first to (and inspired by) the texts themselves—and often they follow protocols advocated by the very critics irritated by the tour. The unsuspecting reader seems to correspond to the vulgar tourist condemned by more discerning, culturally differentiated, “picturesque travelers” of the same period. From this perspective, the literary tourist’s reading of a place is, at the same time, a reading of the literary text.We might argue, then, that the search for an auratic, original House of the Seven Gables, in which “the mythical is mistaken for the real,” is a most Hawthornean way of reading. When Henry James finds himself “wandering perhaps astray” (The American Scene 256) after arriving in Salem, the first thing he does is to ask directions to the House of the Seven Gables, just as less-discerning tourists had been doing for several decades. Though delayed, displaced, and perhaps evaded, the search for the Seven Gables structures James’s visit—and his narrative. Even when recounting other sites and time spent elsewhere, the search returns to interrupt the narrative: first to remind us that he is still approaching the House of the Seven Gables—“to which I am coming” (258)—and later to warn us that it will all turn out to be a “dreadful anticlimax” (259). Finally, before arriving at Turner Street, James engages in a back and forth about the status of the House pointed out by his guide, the “sympathetic American boy, who dropped straight from the hard sky” (260). Even within the labyrinthine Late style, James echoes the denials Lathrop and the Visitors’ Guide repeated for twenty-five years. As James memorably puts it, when his young guide suggests the house on Turner Street is the House of the Seven Gables, “I couldn’t take it in the least” (261).There are many reasons James “couldn’t take it.” But he differs, importantly, from Lathrop and the Visitors’ Guide, which argue repeatedly against the assertion of a single original of Hawthorne’s “visionary mansion.” James does not engage that question but instead rejects any association of these wood and stone realities with the house of ink and imagination. His rejection includes those who seek to encounter the “genius” of Hawthorne in situ or the original of the House of the Seven Gables.5 As James iterates at least six times in Hawthorne, written twenty-five years before his pilgrimage to Salem, “it cannot be too often repeated that Hawthorne was not a realist” (Hawthorne 124). This central tenet of James’s influential guide to reading Hawthorne in 1879 informs his reading of The House of the Seven Gables in 1904. To put too strict an emphasis on any house or any place as the source of the real is to invite readings of Hawthorne that James is unwilling to tolerate. If direct correspondences between the house of fiction and the house on Turner Street can be so readily (and firmly) established, then “unsuspecting” literary tourists and the purveyors of literary tourism may risk mistaking the great Romancer for something much closer to the realist writers of James’s generation.James need not be too worried, though. In practice, the poetics of literary tourism welcomes the ontological uncertainty of places that have what Washington Irving calls “storied and poetical associations” (12). Literary tourists may invite what James derides as “the poor illusion of a necessity of relation between the accomplished thing [the work of art] and those other quite equivocal things [the destinations of the tour]” (The American Scene 261). But many, or most, literary pilgrims understand the “quite equivocal” nature of the sites they visit. They do not insist on the “necessity” of a fixed relation between the actual and the imaginary; on the contrary, unfixing the boundaries is the point of the tour. The “equivocal” is part of the allure.Hawthorne anticipates and even instigates all of this with the amazingly acrobatic narrative devices that start The House of the Seven Gables. From the Preface to chapter 1 and beyond, Hawthorne deliberately kicks the “ladder . . . from the top of a wall,” to borrow the closing figure of James’s Salem tour, leaving readers and tourists to “[turn] a somersault into space” and “tread the air” (The American Scene 262). Hawthorne’s house, in this novel, is there and not there on the “soil of the County of Essex” (CE 2:3), conjured, denied, ultimately entered as the visitable house of fiction: a House of the Seven Gables in ink and wood and stone. By the time Hawthorne composed these acrobatics in The House of the Seven Gables, he was already an accomplished literary tour guide. “The Old Manse” and “The Custom-House” established him as a forerunner of a proto-auto-fiction that offers both guided topographical tours (of sites that become, in the act of writing, instant tourist destinations) and visits to the author as the object of the tour. Hawthorne’s many presentations of the scene of creative production invite more intimate access to the “genius” at work than any traditional pilgrimage to an author’s birthplace, the “author’s seat,” or any other literary sites in wood and stone.Hawthorne’s innovative introductory essays, and their invocation of imagined presence, follow a long line of earlier experiments in the poetics of tourism that reach back to the unpublished collection Hawthorne once called “The Itinerant Story-teller.”6 Several tales and sketches from the 1830s and 1840s enact a tour within the story, or frame the central story with an authorial persona serving as guide—often, as in The House of the Seven Gables, to a visitable house of fiction or to sites with “storied and poetical associations.” Other texts theorize the tour. “My Visit to Niagara” (1835) performs a masterful anatomy of picturesque aesthetics, whereas the meta-fictional tour of Salem in “Alice Doane’s Appeal” dramatizes the relation of storytelling, the Gothic, and history. The Gothic tale “The Lily’s Quest” (1839) was reprinted in The Picturesque Pocket Companion, and Visitors’ Guide, Through Mount Auburn, where it helped visitors blur distinctions between fiction and the tour. Several decades later, Hawthorne’s explicit tours of Salem—“A Rill from the Town-Pump,” “Foot-prints on the Sea-shore,” “Main Street”—were transformed into a list of attractions in the Visitors’ Guide to Salem with directions to the original sites. At these sites, the Guide informs us, “one can hardly make a more pleasant pilgrimage . . . than by spending a half-hour, book in hand, reading one of his beautiful sketches, upon the very spot where Hawthorne himself stood when the inspiration seized him to write it” (Hunt, Guide 141 [1892]).This passage points again to the unresolvable paradox in the structure of literary tourism: like the two versions of the House of Seven Gables—there and not there—the “very spot where Hawthorne himself stood” is real and unreal. Literary pilgrims may walk to Essex Street or to the birthplace or to Gallows Hill, but where exactly did Hawthorne stand when “inspiration seized him”? The same writers who deny a single original structure for The House of the Seven Gables are willing to suspend skepticism about the authenticity of the real when it concerns the “very spot” where genius transpires (or possibly could). They do so because the promise of intimate relation, of imagined proximity, at the scene of creation is central to the poetics of tourism. Just as readers wish to enter and feel present in the storyworld a narrative creates, literary pilgrims wish to enter the world of the making of that story. The real becomes a means of reaching deeper into the unreal; presence on the tour intensifies the sense of presence in the text.7As the collection of essays in this special issue show, this process works in reverse as well: the fictive can enhance, or story, the real. Later editions of the Visitors’ Guide to Salem illustrate the process by closing the chapter on Hawthorne with an extract of what it calls the “weird detached paragraphs” of “Alice Doane’s Appeal.” This early hybrid text, part fiction and part sketch, certainly warrants the Guide’s description. Weird it is—formally, thematically, historically. Less expected is the praise the Guide bestows on the tale for creating a “picture of early Salem [that] is truthful and interesting” (161 [1894]). Here, the weird and Gothic point, somehow, to the real Salem. Hawthorne’s experimental storytelling “on the very spot” also spurs the people of Salem to commemorate, at last, the tragic executions on Gallows Hill. “A duty,” the Guide reports in 1894, “which the Essex Institute seeks to perform in this year of the two hundredth anniversary of the great jail delivery, the one bright spot in the gloom of that epoch in our history” (161).Whether or not that duty was performed as Hawthorne’s story envisions, “Alice Doane’s Appeal” secures a new afterlife as an incitement to both literary tourism and civic activism. In citing Hawthorne’s weird text, moreover, the Guide seems to accept the blurring of distinctions between the real and the unreal, and the imagined and the historical, that it insists on in the case of the house on Turner Street. With this appearance in the Guide, “Alice Doane’s Appeal” joins other Hawthorne texts, including The House of the Seven Gables, that have been absorbed into the de-differentiating discourse of literary tourism. After Caroline Emmerton “restored” the House of the Seven Gables in 1910 and opened the museum to the public, the process seems to have been complete. The 1916 Visitors’ Guide to Salem opens with a “Brief Itinerary” that includes: “‘House of the Seven Gables’ (so called), 54 Turner street, built about 1669; a favorite haunt of Hawthorne; now restored, with six furnished rooms, a secret staircase, furniture, relics and a ‘cent shop.’ Admission 25c” (np). . . . “This collection of houses now forms one of the greatest attractions for the visitor to Salem” (Visitors’ Guide 60 [1916]).The unusual range of materials in this special issue—a public lecture, two articles on Hawthorne’s novel, and an interview with leaders of The House of the Seven Gables Museum—presents the results of a collaboration the Nathaniel Hawthorne Society started with the museum in the fall of 2023. Members of the Hawthorne Society had long discussed initiating some form of “public humanities” project to reach across the divide between academic Hawthorne scholars, lay readers, and the vibrant institutions where the public meets Hawthorne on the ground. “The House of the Seven Gables” (and “The Old Manse” in Concord) remain popular destinations for tourists, and the people who run those sites teach tens of thousands of visitors about Hawthorne each year and help grow and sustain his readership. We wanted to join them in that work and to foster new collaborations for the future.Our first project was to establish the Hawthorne Society Annual Lecture at “The House of the Seven Gables.” Each spring, we invite a Hawthorne scholar to present a free, public lecture in Salem. Our goal is to share current scholarship with a wider public in an accessible style. We were very fortunate that the esteemed Americanist Robert Levine agreed to give our second annual lecture, which we planned to coincide with the American Literature Association conference in Boston. To complement our effort to bring an accomplished scholar to the House of the Seven Gables, we invited leaders of the museum to join us at the ALA conference. Executive Director Dakota Russell and Curator of Collections Susan Baker joined our roundtable “The House of Seven Gables in Ink, Wood, and Stone.” In keeping with our goal of taking a new approach to Hawthorne and to The House of the Seven Gables, we were pleased to invite early-career scholars to participate on the roundtable. Two were students at the time: Luke Woodard was an MA candidate and a teacher at a private secondary school and Mitchell Edwards was a PhD candidate at Rutgers. The essays and interview that follow have been expanded from the talks presented on that occasion.The Hawthorne Society Annual lecture took place Sunday afternoon after the close of conference activities. Just as we hoped members of the public would attend the lecture, we wanted to get scholars from the ALA in Boston to the House of the Seven Gables in Salem. Fortunately, a commuter ferry opened recently, and we purchased a set of group tickets, making it possible for twenty scholars from all over the world to take the trip through Boston Harbor and up the coast to Salem. The lecture took place in the “Great Chamber” of the “Hooper Hathaway House” (c. 1682), which was relocated to the museum campus in 1911 to save it from demolition. For much of the twentieth century, the house hosted Settlement classes and literary tourists in the “six furnished rooms” with baths. We had arrived, finally, at the House of Seven Gables as advertised in the Visitors’ Guide to Salem!Robert Levine gave his talk to a standing-room-only audience of students, scholars, and museum staff.8 The text of Levine’s talk, “Haunted Houses: The House of the Seven Gables and Uncle Tom’s Cabin,” is presented in this issue of Nathaniel Hawthorne Review without significant change. It strikes a fine balance between accessibility for a general audience (deftly summarizing scenes from the two haunted houses) and making an important, revisionary argument about Hawthorne’s engagement with questions of race and slavery in The House of the Seven Gables. Levine shows how the numerous references to color, blood, and race in the novel complicate and undermine the notions of white, racial purity that underlay Colonel Pyncheon’s “genealogical ambition to perpetuate his supposedly white family.” Thus, the original house of Pyncheon is haunted by more than Maule’s curse. Levine’s lecture, informed by his forthcoming book on Stowe and Black America, closes with a review of some interesting biographical convergences between the authors of the two houses that should serve as a corrective for our partial accounts of Stowe’s anger with Hawthorne’s dedication of Our Old Home to Franklin Pierce (“that traitor”!). Levine points out that despite her earlier outrage, Stowe gave her daughter an elegantly bound edition of Hawthorne’s collected works in 1865.The two essays that follow Levine’s “Haunted Houses” move comfortably back and forth between elements of the House’s unstable ontological status that I have outlined in this introduction: Hawthorne’s fictional narrative, the House of the Seven Gables in ink, and the novel’s afterlife as The House of the Seven Gables Museum in wood and stone. They conduct close, formal analyses of the narrative structures Hawthorne builds in his “visionary house,” and, as a nimble literary tourist might do, they read the history of the house through the lens of—and as an interpretation of—Hawthorne’s novel. The unreal and the real are in full dialectical play in both essays. Crucially, each moves beyond the binary of ink and wood to consider the House of the Seven Gables in the world—as it figures in the history of novelistic technique and on the “soil of the County of Essex” (3) and in the history of American literary criticism. Together they present new perspectives on the House of the Seven Gables in ink, wood, and stone as it persists in the wider literary and physical worlds.Luke Woodard’s “Crossing Thresholds in The House of the Seven Gables: Hawthorne’s Narrative Architecture and the Encounter with History” (this issue) begins by directing our attention to the interventions of Hawthorne’s narrator and to Hawthorne’s narrative technique in The House of the Seven Gables. Woodard shows that the trope of the threshold, often considered in terms of characterization and theme, also represents Hawthorne’s work as a “narrative architect . . . who constructs a house of words . . . that will be inhabited by readers.” Hawthorne’s house of ink, in Woodard’s conception, contains the house of stone within the fictional storyworld. Woodard takes the manifest threshold crossings as a trope for the way Hawthorne persistently blurs the very distinctions he claims to maintain between the real and the imaginary and the past and the present. He argues that Hawthorne uses this liminal “narrative architecture” along with the scenes of storytelling inside The House of the Seven Gables to dramatize “the importance of form and style in facilitating an imaginative encounter with history.” In a final critical turn, Woodard looks ahead to Hawthorne’s influence on The House of the Seven Gables Museum as evidence that “Hawthorne’s narrative techniques have achieved physical expression . . . [in] a real structure.” The House of the Seven Gables in ink and wood crosses the threshold into the historical, contingent world.Mitchell Edwards’s “Flip This House: Caroline Emmerton’s Activist Hermeneutics and The House of the Seven Gables” takes this turn to the House of the Seven Gables in the world even further. He uses archival research, book history, and an original conception of activist literary criticism to historicize Caroline Emmerton’s work at the House of the Seven Gables and “flip” our understanding of her contributions. Edwards starts with the assertion that “the house and the book are two linked components of a composite cultural text” and argues that Emmerton’s renovations of the House also begin her renovation of Hawthorne’s novel, or, more precisely of the visitor-reader’s interpretation of the book. Edwards further shows that Emmerton’s varied activities, her essays, plays written for performance at the Settlement house, and republication of the “Visitors’ Edition” of the novel constitute a form of social activism and literary interpretation—what he calls an “activist hermeneutics.” Edwards reads Emmerton’s contribution to this emerging mode in the context of other twentieth-century activist literary movements and concludes with the bold claim that Emmerton is “invested in conscripting Hawthorne for radical social change, placing him at the center of a public humanities project marked by its Progressive Era origins.”Those origins continue to influence how visitors experience the House of the Seven Gables and to inform the larger work of the “House of the Seven Gables Settlement Association” (Emmerton’s original organization, which owns and operates the museum). We close this special issue with an edited transcript of an interview with our partners in our contemporary public humanities project: Executive Director Dakota Russell and Curator of Collections of the Seven Gables Susan Baker. Russell and Baker talk about the history of the House since Caroline Emmerton created the Settlement Association and opened the museum, about continuities with Emmerton’s mission in their settlement work and programming today, and about their representation of Hawthorne’s work and life at the Seven Gables. They also discuss their new initiative to revitalize the Hawthorne birthplace museum and to become a hub for Hawthorne studies and literary tourism. The Hawthorne Society has collaborated on this project from its inception, and we will continue as it goes forward. (You may hear more about fundraising efforts in the future.)We hope to see you in Salem for our next House of the Seven Gables lecture—and then again in June of 2028 for our next international Hawthorne Society conference!
Keywords: dept.eng

The House of the Seven Gables Then and Now: A Conversation with Executive Director Dakota Russell and Curator of Collections Susan Baker of The House of the Seven Gables Settlement Association (transcript from September 18, 2025) - Baraw, Charles; Russell, Dakota; Baker, Susan (Nathaniel Hawthorne Review, 2025)
ABSTRACT. A conversation with Dakota Russell, Executive Director, Susan Baker, Curator of Collections from The House of the Seven Gables Settlement Association, and Charles Baraw, past president of the Nathaniel Hawthorne Society.
Keywords: dept.eng

Property and precarisation: reading Seth Tobocman’s War in the Neighborhood and Fly’s CHRON!IC!RIOTS!PA!SM! - Stretch, Cynthia (Textual Practice, 2025)
Keywords: Fly (Elen Orr); Isabell Lorey; Property (philosophy); Reading (process); Seth Tobocman; bad debt; dept.eng; precarisation; squatting